Analyses on Heating Energy Saving of Two Hot Waxy-Crude Oil Pipelines Laid Parallel in One Ditch. (19th March 2013) - Sun, Changzheng; Yu, Bo
Abstract : Laying two pipelines in one ditch is a new technology recently employed by the petroleum companies of China and has great advantages of minimizing environmental disruption as well as bringing tremendous economic and social benefits. In this study, by means of numerical simulations analyses are carried out to evaluate heating energy saving for the operation of two hot crude oil pipelines laid parallel in one ditch. Comparisons are made based on three various operating scenarios, among which the best operation is proposed. The effects of some important parameters such as the gap between the two pipelines (also called pipeline interval) and pipe length are investigated. It is found that two hot crude oil pipelines laid parallel in one ditch can dramatically save heating energy when compared with two pipelines laid, respectively, in two separate ditches.